Effects of advertising features on smokers' and non-smokers' perceptions of a reduced nicotine cigarette modified risk tobacco product. Issue 1 (15th April 2021) - Mercincavage, Melissa; Pacek, Lauren R; Thrasher, James; Cappella, Joseph N; Delnevo, Cristine; Donny, Eric C; Strasser, Andrew A
Abstract : Introduction: Research is needed to determine the impact of marketing on perceptions and use of reduced nicotine content (RNC) cigarettes, particularly as US regulators have permitted the sale of an RNC cigarette modified risk tobacco product (MRTP) that seeks further authorisation to advertise using modified risk claims. This study examined the effects of two advertising elements (product name and disclaimer content) on perceptions of an RNC cigarette MRTP. Methods: Adult participants (n=807, 28.7% smokers, 58.2% male, 74.2% non-Latinx white) completed an online MTurk survey. Participants were randomised to view one of six RNC cigarette advertisements, using a 2×3 between-subject factorial design to manipulate product name ('Moonlight' vs 'Moonrise') and disclaimer content (industry-proposed: 'Nicotine is addictive. Less nicotine does NOT mean a safer cigarette' vs focused: 'Less nicotine does NOT mean a safer cigarette' vs no content), then completed recall and product perception questionnaires. Results: All participants who viewed the industry-proposed disclaimer (vs no content) perceived greater addiction risk (p's<0.05). Non-smokers who viewed this disclaimer also perceived greater health risks and held fewer false beliefs (p's<0.05). Smokers who viewed Moonlight (vs Moonrise) ads perceived lower health risks (p<0.05). Conclusions: Disclaimer content may effectively inform consumers about addiction risk of a new RNC cigarette MRTP, and further inform non-smokers about health risks. This element, however, had little effect on perceived health risks among smokers, among whom the Moonlight product name was associated with health risk misperceptions similar to the banned 'light' descriptor.